How to sleep well in times of high job demands: The supportive role of detachment and perceived social support - Matick, Eva; Kottwitz, Maria U.; Lemmer, Gunnar; Otto, Kathleen (Work and stress, 2021)
This study aims to examine whether employees who perceive there to be social support from supervisors and colleagues would be better able to detach from work during non-work time and thus sleep better in times of high job demands. Considering contextual factors, such as type of employment (full- and part-time) and supervisor status (with and without), which could influence the associations between work, non-work, and sleep, we also explored these relationships within subgroups of employees. A total of 1856 employees participated in a two-wave-panel study representative of the German adult population. Controlling for the baseline level of sleep quality, regression analyses revealed that job demands predicted changes in sleep quality over a 6-month period and that detachment fully mediated this effect. Furthermore, perceived social support buffered the indirect effect of job demands on sleep quality via detachment. In summary, the results suggest that the interplay of job demands, detachment, and perceived social support is important in promoting sleep quality. Type of employment and supervisor status seem to be factors shaping the above-mentioned effects and should, therefore, be considered in future research.